Laporan Kasus: Proses Asuhan Gizi Terstandar pada Pasien Diabetes Melitus Tipe 2 dengan Riwayat Hipoglikemi Terkoreksi dan Chronic Kidney Disease (CKD) di RSUD Cibinong: Case Report: Standardized Nutrition Care Process for a Type 2 Diabetes Mellitus Patient with Corrected Hypoglycemia and Chronic Kidney Disease (CKD) at RSUD Cibinong - Aliah, Nur; Marliyanti, Sri Anna (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Diabetes Mellitus (DM) encompasses a group of metabolic disorders characterized by hyperglycemia. Uncontrolled DM can lead to chronic hyperglycemia, imposing an increased glucose burden on the kidneys. This persistent burden may impair renal function, as evidenced by elevated urea and creatinine levels. Elevated urea levels can result in uremic syndrome, manifesting as acid-base imbalance, thereby increasing gastric acid production and inducing nausea, which subsequently reduces appetite, decreases dietary intake, and may ultimately trigger hypoglycemia. This case report aims to implement and analyze the standardized nutritional care process (NCP) and to highlight interprofessional collaboration in the medical treatment of a hospitalized DM patient at Cibinong Regional Hospital. This report presents the case of a 54-year-old female patient with Type 2 Diabetes Mellitus with corrected hypoglycemia, chronic kidney disease (CKD) with a differential diagnosis of acute kidney injury (AKI), and normal nutritional status. The patient was admitted to the emergency room (ER) due to loss of consciousness. Biochemical examination revealed hypoglycemia, elevated urea and creatinine levels, and low hemoglobin. The nutritional diagnoses established were NI.21 Inadequate oral intake, NC.2.2 Altered nutrition-related laboratory values, and NB 1.6 Limited adherence to nutrition-related recommendations. Nutritional therapy was implemented through interprofessional collaboration. Dietary management was adjusted to the patient’s condition, considering nutritional requirements based on nutritional status, activity level, stress factors, and age. The prescribed diet consisted of a soft-consistency, low-protein diabetic diet administered orally. During the three-day intervention, nutrient intake improved, with an average adequacy of 72.33% for energy, 74.67% for protein, 75.67% for fat, and 67% for carbohydrates. The diet provided is a low-protein diabetes mellitus diet with a soft consistency, administered orally. In conclusion, the application of the standardized nutrition care process, supported by interprofessional collaboration, plays a crucial role in optimizing patient outcomes, preventing malnutrition, and maintaining glycemic control.